2003
DOI: 10.1002/art.11181
|View full text |Cite
|
Sign up to set email alerts
|

Serologic changes following B lymphocyte depletion therapy for rheumatoid arthritis

Abstract: Objective. To explore the changes in serologic variables and clinical disease activity following B lymphocyte depletion in 22 patients with rheumatoid arthritis (RA).Methods. B lymphocyte depletion was attained using combination therapy based on the monoclonal anti-CD20 antibody rituximab. Levels of a serologic indicator of inflammation, C-reactive protein (CRP), of antimicrobial antibodies, of autoantibodies including IgA-, IgM-, and IgG-class rheumatoid factors (RF), and of antibodies to cyclic citrullinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
261
4
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(305 citation statements)
references
References 31 publications
32
261
4
8
Order By: Relevance
“…Apparently, no clear relation exists between the degree of depletion of MS4A1 positive cells from peripheral blood and the therapeutic effect. The relation between circulating levels of MS4A1 positive lymphocytes, serological markers of autoimmune disease and effectiveness of rituximab in autoimmune disease is complex, but a number of studies suggest an inverse relationship between proportions of B-cells, autoantibody titres and therapeutic effect in rheumatoid arthritis and lupus (10,17,26,27). In our study, the proportion of CD-20 positive lymphocytes was not associated with TBII levels.…”
Section: Discussioncontrasting
confidence: 55%
“…Apparently, no clear relation exists between the degree of depletion of MS4A1 positive cells from peripheral blood and the therapeutic effect. The relation between circulating levels of MS4A1 positive lymphocytes, serological markers of autoimmune disease and effectiveness of rituximab in autoimmune disease is complex, but a number of studies suggest an inverse relationship between proportions of B-cells, autoantibody titres and therapeutic effect in rheumatoid arthritis and lupus (10,17,26,27). In our study, the proportion of CD-20 positive lymphocytes was not associated with TBII levels.…”
Section: Discussioncontrasting
confidence: 55%
“…6 This is also evident in rheumatoid arthritis, where B-cell depletion therapy contributes to a positive clinical response in correlation with a significant drop in auto-Abs. 7 Importantly, low levels of auto-Abs can be detected in the serum many years before clinical symptoms of rheumatoid arthritis, 8 suggesting that an early break in B-cell tolerance is underlying the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, a single case report on an SPS patient demonstrated a rapid decline of intrathecal GAD65 IgG antibodies following anti-CD20 treatment, which suggested a successful targeting and elimination of autoantibody producing B cells within the CNS (Baker 2005). Furthermore, clinical trials with B cell depletion in other autoimmune diseases, such as RA and SLE, reported that certain autoantibodies, anti-DNA and rheumatoid factor, decayed after anti-CD20 B cell therapy (Cambridge 2003;Sfikakis 2005;. It is tempting to speculate that the continuously produced GAD65 IgG antibodies in SPS patients are being generated rapidly from renewing CD20 + B cell precursors, most consistent with the short-lived plasmablasts pathway.…”
Section: Breaking Tolerance To Gad65mentioning
confidence: 99%